1993
DOI: 10.3109/10715769309056512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Actions of Ferulic Acid and Catechins

Abstract: We have evaluated the abilities of ferulic acid, (+/-) catechin, (+) catechin and (-) epicatechin to scavenge the reactive oxygen species hydroxyl radical (OH.), hypochlorous acid (HOCl) and peroxyl radicals (RO2.). Ferulic acid tested at concentrations up to 5 mM inhibited the peroxidation of phospholipid liposomes. Both (+/-) and (+) catechin and (-) epicatechin were much more effective. All the compounds tested reacted with trichloromethyl peroxyl radical (CCl3 O2.) with rate constants > 1 x 10(6) M-1 s-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(109 citation statements)
references
References 28 publications
2
104
0
3
Order By: Relevance
“…Thus, it is suggested that ferulic acid has multiple modes of action regarding Aβ in the AD pathogenesis. Although the mechanism of the ferulic acid-induced inhibition of Aβ deposition in the cortex was not addressed in the present study, it could be due to ferulic acid's anti-oxidant 4,5) and anti-inflammatory 6,7) activities. However, the reason why ferulic acid decreases Aβ deposition more effectively in the frontal cortex than the hippocampus (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, it is suggested that ferulic acid has multiple modes of action regarding Aβ in the AD pathogenesis. Although the mechanism of the ferulic acid-induced inhibition of Aβ deposition in the cortex was not addressed in the present study, it could be due to ferulic acid's anti-oxidant 4,5) and anti-inflammatory 6,7) activities. However, the reason why ferulic acid decreases Aβ deposition more effectively in the frontal cortex than the hippocampus (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…3) Ferulic acid is a natural molecule abundantly present in the various plants. It has anti-oxidant 4,5) and anti-inflammatory 6,7) activities. We previously reported that long-term (4 weeks) administration of ferulic acid protects against intracerebroventricularly (i.c.v.)…”
mentioning
confidence: 99%
“…Concentrations of these compounds were selected for testing their best antioxidant activities. 61,62 The antioxidant solutions were continuously flowed into the chip for 1 h, and then the cells were incubated with 10 lM DCFDA for 15 min before washing with 1Â PBS for another 30 min. Again, fluorescent images were captured using an inverted fluorescent microscope.…”
Section: Antioxidant Experimentsmentioning
confidence: 99%
“…It has also been used to treat ischemic brain and heart diseases (Kang, 1993;Shin, 1996). The main constituents of SMT are known as phenolic compounds, phthalides, alkaloids, terpene glycosides, and iridoid glycosides (Sheng et al, 2005), and some of these are known to have antioxidant or antiischemic effects (Graf, 1992;Scott et al, 1993;Yan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%